Sleep-Related Breathing Problem Trajectories Across Early Childhood and Academic Achievement-Related Performance at Age Eight - Harding, Rebecca; Schaughency, Elizabeth; Haszard, Jillian J.; Gill, Amelia I.; Luo, Rebekah; Lobb, Carmen; Dawes, Patrick; Galland, Barbara (Frontiers in Psychology, 2021)
Background: Childhood sleep disordered breathing (SDB) has been linked to poorer academic performance; however, research has not investigated the extent improvement in SDB may alter outcomes across key academic skills. This study aimed to investigate if children’s early SDB status could predict later academic outcomes, and if an improvement in SDB status across the early childhood years would coincide with better, later performance in key academic skills related to reading, numeracy, and listening comprehension. Methods: Eighty five case children with an SDB symptom score >25 (maximum 77) were matched to 85 control children (score <12) at recruitment (age 3). SDB severity (symptom history and clinical assessment) was evaluated at ages 3, 4, 6, and 8 years and performance on individually-administered academic skills assessed at age 8 (91 % retention from age 3). Case children were categorized into “improved” or “not-improved” groups based on SDB trajectories over the 5 years. Contributions of SDB status and trajectory group to academic performance were determined using regression analysis adjusted for demographic variables Results: History of SDB from age 3 predicted significantly poorer performance on some key academic skills (oral reading and listening skills) at age 8. Children whose SDB improved (45%) performed better in oral reading fluency than those whose SDB did not improve, but difficulties with specific tasks involving oral language (listening retell) remained when compared to controls. Conclusion: Findings support links between early SDB and worse academic outcomes and suggest key academic areas of concern around oral language. Findings highlight the need for child mental health professionals to be aware of children’s sleep problems, particularly SDB (past and present), when assessing potential barriers to children’s achievement, to assist with appropriate and timely referrals for evaluation of children’s sleep difficulties and collaborative evaluation of response to intervention for sleep difficulties.